"They Go for Gender First": The nature and effect of sexist abuse of female technology journalists. (9th August 2018) - Adams, Catherine
Abstract : There have been many recent media reports about the online harassment of women journalists working in technology, particularly the video gaming industry. However, little research has focused on this aspect, by looking at specific occupations, or analysing the implications for women and society. This paper is a feminist study of the experiences of sexist abuse of a sample of women journalists writing about technology. It is a commentary on the results of a questionnaire-based study of 102 women (and their approximately 300 comments) that work in what has emerged as one of the frontlines of the struggle for gender equality. The research looks at the extent of the abuse, the harm it causes and how women are reacting to it. Most of the participants have experienced abuse, many have changed their working practices and some have disguised their identity to avoid it. An examination of their comments suggests that sexist abuse is now often normalised, alongside a new kind of "invisible" feminism. It also reveals a mood of defiance and an appetite for radical change to address the problems of exclusion and loss of identity. Overall, results indicate that the abuse is damaging women's lives and impacting journalism and society in a negative way.